2011
DOI: 10.21082/ijas.v12n2.2011.p63-69
|View full text |Cite
|
Sign up to set email alerts
|

Rural Farmers’ Perception of Climate Change in Central Agricultural Zone of Delta State, Nigeria

Abstract: Farmer perception of their environment is a factor of climate change. Adaptation to climate change requires farmers to realize that the climate has changed and they must identify useful adaptations and implement them. This study analyzed the per-ception of climate change among rural farmers in central agri-cultural zone of Delta State, Nigeria. Climate change studies often assume certain adaptations and minimal examination of how, when, why, and conditions under which adaptations usually take place in any econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 4 publications
8
37
1
1
Order By: Relevance
“…This implies that the respondents in the study area perceived climate change led to decrease crop production. These findings agree with that of Ofuoku (2011), Abraham et al (2012) and Farauta et al (2011) that farmers perceived reduction in crop production, increase in pest and disease infestation, decrease food availability, decrease in soil fertility and increase in cost of food crops as common effects of climate change on crop production. Climate change is a serious threat to agriculture and food security especially the rural communities which majorly rely on agriculture to meet their subsistence needs.…”
Section: Results and Discussion Farmer Households' Perception Of Climsupporting
confidence: 90%
“…This implies that the respondents in the study area perceived climate change led to decrease crop production. These findings agree with that of Ofuoku (2011), Abraham et al (2012) and Farauta et al (2011) that farmers perceived reduction in crop production, increase in pest and disease infestation, decrease food availability, decrease in soil fertility and increase in cost of food crops as common effects of climate change on crop production. Climate change is a serious threat to agriculture and food security especially the rural communities which majorly rely on agriculture to meet their subsistence needs.…”
Section: Results and Discussion Farmer Households' Perception Of Climsupporting
confidence: 90%
“…With respect to the factors influencing the likelihood of adoption, the result on the positive effect of the number of years of forest use (experience) resonates with those of Shortle and Miranowaski (1986), Gbetibouo (2008), Ayanwuyiet al ( , Dhaka et al(2010,Baffoe-Asare(2013), Mudzonga (2012), Rana et al (2012), Shankar et al (2013),who found that experience has a positive effect on adoption decision. Thus, Ofuoku (2011) opine that those who have many years of farming experience have interacted much more with the climate in relation to their activities and therefore, have good knowledge of environmental factors as they relate to their daily operations. It is not surprising that households with access to electricity are more likely to adapt to climate change than those that haven't.…”
Section: Discussionmentioning
confidence: 99%
“…Perception can be defined as the process by which organisms interpret and organise sensation to produce a meaningful experience of the world (Lindsay & Norman, 1977;Ndamani & Watanabe, 2015;Pickens, 2005). According to Ofuoku (2011), it is anticipated that a man's reaction to protect his well-being and future is based on his perception and interpretation of climate change. Although such perception and interpretation could differ substantially from reality (Pickens, 2005), they must be put into consideration to address socio-economic challenges (Kusakari et al, 2014;Ndamani & Watanabe, 2015).…”
Section: Introductionmentioning
confidence: 99%